2016
DOI: 10.1002/jnr.23718
|View full text |Cite
|
Sign up to set email alerts
|

Extension of recovery time from fatigue by repeated rest with short‐term sleep during continuous fatigue load: Development of chronic fatigue model

Abstract: Homeostasis is known to be involved in maintaining the optimal internal environment, helping to achieve the best performance of biological functions. At the same time, a deviation from optimal conditions often attenuates the performance of biological functions, and such restricted performance could be considered as individual fatigue, including physical and mental fatigue. The present study seeks to develop an animal model of chronic or subacute fatigue in which the recovery time is extended through the gradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…After 10 days of fatigue loading, the rats showed a significant decrease in nighttime spontaneous activity compared to the pre-fatigue level. This result confirms that our fatigue-loading procedure is sufficient to induce a fatigue state in rats and is consistent with previous reports using this fatigue loading procedure (rest and sleep deprivation) in spite of some modifications in the present study ( 25 , 30 ). Depressed spontaneous activity is a behavioral manifestation of fatigue, which may reflect an insufficient motivation of fatigued animals to move.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…After 10 days of fatigue loading, the rats showed a significant decrease in nighttime spontaneous activity compared to the pre-fatigue level. This result confirms that our fatigue-loading procedure is sufficient to induce a fatigue state in rats and is consistent with previous reports using this fatigue loading procedure (rest and sleep deprivation) in spite of some modifications in the present study ( 25 , 30 ). Depressed spontaneous activity is a behavioral manifestation of fatigue, which may reflect an insufficient motivation of fatigued animals to move.…”
Section: Discussionsupporting
confidence: 94%
“…We established the fatigue model with rats based on the previous reports with some modifications ( 24 , 25 ). The procedure of fatigue loading was shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the underlying mechanisms of those findings are not clear at present, potential candidates include short sleep duration, low sleep quality, autonomic nervous dysfunction such as elevated sympathetic nervous function, and altered endocrine and immune functions. We reported that loading of psychological fatigue in rats was associated with disturbance of neuroendocrinological functions [86]. Furthermore, in the HSCAA cohort study, fatigue score was found to be closely associated with plasma leptin level in patients with cardiovascular risk factors [87].…”
Section: Fatigue Atherosclerosis and Cardiovascular Diseasesmentioning
confidence: 99%
“…Recently, animal models have been developed to include both and which, as the authors hope, ‘could be used to seek better preventive measures and to explore the neural and molecular mechanisms involved in severe, long‐lasting fatigue’ (Kanzaki et al . ).…”
mentioning
confidence: 97%